2009
DOI: 10.1016/j.virol.2009.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Deep-sequencing of plant viral small RNAs reveals effective and widespread targeting of viral genomes

Abstract: Plant virus infection involves the production of viral small RNAs (vsRNAs) with the potential to associate with distinct Argonaute (AGO)-containing silencing complexes and mediate diverse silencing effects on RNA and chromatin. We used multiplexed, high-throughput pyrosequencing to profile populations of vsRNAs from plants infected with viruses from different genera. Sense and antisense vsRNAs of 20 to 24 nucleotides (nts) spread throughout the entire viral genomes in an overlapping configuration; virtually al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
186
7
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(244 citation statements)
references
References 58 publications
38
186
7
8
Order By: Relevance
“…In addition to the DI-RNA-derived siRNA peaks in ANV RNA2, the distribution of viral siRNAs was not uniform along the remaining viral genomic RNAs (Fig. S4), as noted previously (16)(17)(18)(19)(20). However, our analyses indicated that the high siRNA density regions of the viral RNA genomes were associated with neither unusual adenine+uridine (AU) content nor strong secondary structures.…”
Section: Discovery Of Four Rna Viruses From a Drosophila Schneider 2 supporting
confidence: 64%
See 1 more Smart Citation
“…In addition to the DI-RNA-derived siRNA peaks in ANV RNA2, the distribution of viral siRNAs was not uniform along the remaining viral genomic RNAs (Fig. S4), as noted previously (16)(17)(18)(19)(20). However, our analyses indicated that the high siRNA density regions of the viral RNA genomes were associated with neither unusual adenine+uridine (AU) content nor strong secondary structures.…”
Section: Discovery Of Four Rna Viruses From a Drosophila Schneider 2 supporting
confidence: 64%
“…The Dicer proteins involved in the production of siRNAs targeting both +RNA viruses and DNA viruses have been identified in Arabidopsis thaliana (2,3), and plants encode AGOs in the AGO subfamily but none from the PIWI subfamily (15). Cloning and sequencing of plant viral siRNAs suggest that they may be processed either from vRI-dsRNAs or hairpin regions of single-stranded RNA precursors (16)(17)(18)(19)(20). Production of viral siRNAs has also been demonstrated in fungi, silkworms, mosquitoes, and nematodes in response to infection with +RNA viruses, and viral small silencing RNAs produced in fungi and mosquitoes have recently been cloned and sequenced (21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…In plants, where studies have focused on positive ssRNA viruses, there is some evidence for the first scenario. For example, infection by the Tombusvirus CymRSV generates ∼80% to 90% of viral small RNAs of sense polarity, which may reflect the excess of genome versus antigenome RNA present in infected cells (24,27,30). However, the profiles of vsiRNAs produced in response to several other plant viruses are consistent with processing of a dsRNA precursor: these profiles are characterized by an approximately equal number of vsiRNAs matching the positive or the negative strand of the viral RNA, and covering the whole length of the viral genome (24,26,29).…”
Section: Discussionmentioning
confidence: 99%
“…(vsiRNAs) is the most remarkable feature of virus-induced gene silencing [4,[8][9][10][11][12][13]. Current research indicates that vsiRNAs are derived either from the dsRNAs formed during the virus replication stage or from single-stranded viral RNAs (ssRNAs) with a hairpin-like fold-back structure [8,10,[14][15][16].…”
Section: Special Topicmentioning
confidence: 99%
“…Current research indicates that vsiRNAs are derived either from the dsRNAs formed during the virus replication stage or from single-stranded viral RNAs (ssRNAs) with a hairpin-like fold-back structure [8,10,[14][15][16]. Both of these forms of viral RNA can be processed into vsiRNAs of a specific size by distinct DCLs proteins.…”
Section: Special Topicmentioning
confidence: 99%